2007
DOI: 10.1158/1055-9965.epi-06-0872
|View full text |Cite
|
Sign up to set email alerts
|

The Common Variant rs1447295 on Chromosome 8q24 and Prostate Cancer Risk: Results from an Australian Population-Based Case-Control Study

Abstract: A recent study from deCode reported an association between common variants in the region 8q24 and prostate cancer risk. The strongest association was found with the single nucleotide polymorphism rs1447295. We genotyped 821 prostate cancer cases and 732 population controls for rs1447295 to test the association between this common variant and prostate cancer risk, and examine whether this association depends on Gleason score. Our case-control study confirmed the association between rs1447295 and prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 13 publications
3
38
2
Order By: Relevance
“…Further genotyping within this region and functional analyses are underway. We also note that among our African American subjects, we did not observe an association to the 128.6 Mb region, which maps to the distal 8q24.21 locus originally reported by Amundadottir et al 2006; although the region has been shown by others to influence risk for prostate cancer (Gudmundsson et al 2007;Schumacher et al 2007;Severi et al 2007;Suuriniemi et al 2007;Wang et al 2007;Yeager et al 2007). …”
Section: ‫31מ‬contrasting
confidence: 41%
See 2 more Smart Citations
“…Further genotyping within this region and functional analyses are underway. We also note that among our African American subjects, we did not observe an association to the 128.6 Mb region, which maps to the distal 8q24.21 locus originally reported by Amundadottir et al 2006; although the region has been shown by others to influence risk for prostate cancer (Gudmundsson et al 2007;Schumacher et al 2007;Severi et al 2007;Suuriniemi et al 2007;Wang et al 2007;Yeager et al 2007). …”
Section: ‫31מ‬contrasting
confidence: 41%
“…Ignoring differences in local ancestry across African American subjects may account for the differences observed in previous studies. Yet, strong and replicable association with both DG8S737 and rs1447295 are seen among cohorts of European ancestry (Schumacher et al 2007;Severi et al 2007;Suuriniemi et al 2007;Wang et al 2007). In a study of 1121 European descent familial and sporadic PCa cases, Wang et al (2007) reported significant association with both familial (P = 0.0004) and aggressive prostate cancer (P = 0.0005) and SNP rs1447295 (Wang et al 2007).…”
Section: Polymorphismmentioning
confidence: 97%
See 1 more Smart Citation
“…These four variants were chosen because they have the most data available for each of the three 8q24 regions. We also conducted a metaanalysis for advanced prostate cancer from available data for the rs1447295 1,6,7,9 and DG8S737 variants, 1,5,8,9 including our results. Allele-specific ORs were abstracted from published studies.…”
Section: Methodsmentioning
confidence: 99%
“…[49][50][51] This 7.5-Mb locus overlaps with the 8q24 region, which has been reported in linkage and GWASs of PrCa 17,23,24,29,32 and has been replicated in many studied populations. 22,25,26,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] The prostate stem cell antigen maps to this region 69 as does the oncogene MYC. The region has been extensively studied and is relatively gene-poor.…”
Section: Discussionmentioning
confidence: 99%